Other words for home - Warga, Jasmine (Balzer + Bray, an imprint of HarperCollins Publishers, 2019)
Sent with her mother to the safety of a relative's home in Cincinnati when her Syrian hometown is overshadowed by violence, Jude worries for the family members who were left behind as she adjusts to a new life with unexpected surprises.